1995
DOI: 10.1111/j.1476-5381.1995.tb13263.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between 5‐HT3 receptor antagonists in modulation of visceral hypersensitivity

Abstract: Noxious colo‐rectal distension was applied in conscious rats by acute balloon inflation and the effects observed as abdominal muscle contraction with the threshold typically between 10–40 mmHg. The effects of 5‐HT3 receptor antagonists on responses to noxious colo‐rectal distension were then studied in both normal rats and those pretreated with 5‐hydroxytryptophan (5‐HTP). Granisetron and ondansetron (10 μg kg−1 and 1 mg kg−1, s.c.) had no effect on visceromotor thresholds to colo‐rectal distension in normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…It has been implied that the 5-HT 3 receptor is involved also in other types of visceral pain, such as stressinduced delayed visceral hyperalgesia [22], visceral hyperalgesia associated with somatic mechanical hyperalgesia by acid injection into the gastrocnemius muscle [23], and intracolonic glycerol infusion-induced visceral hypersensitivity [24]. It is noteworthy that, in previous studies, the alleviating effect of 5-HT 3 receptor antagonists was not observed in normal/control rats [12,13,22,25]. However, the effect of some 5-HT 3 receptor antagonists is still controversial in normal rats.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…It has been implied that the 5-HT 3 receptor is involved also in other types of visceral pain, such as stressinduced delayed visceral hyperalgesia [22], visceral hyperalgesia associated with somatic mechanical hyperalgesia by acid injection into the gastrocnemius muscle [23], and intracolonic glycerol infusion-induced visceral hypersensitivity [24]. It is noteworthy that, in previous studies, the alleviating effect of 5-HT 3 receptor antagonists was not observed in normal/control rats [12,13,22,25]. However, the effect of some 5-HT 3 receptor antagonists is still controversial in normal rats.…”
Section: Discussionmentioning
confidence: 88%
“…However, the 5-HT 3 receptor antagonists have not been active in all models of colorectal hyperalgesia. 5-HT 3 receptor antagonists were effective in reducing the visceral hypersensitivity induced by chemicals such as 5-HTP, acetic acid, glycerol and 2,4,6-trinitrobenzene sulfonic acid (TNBS) [13,14,24,26]. In a different way granisetron did not modify the delayed rectal allodynia induced by mast cell degranulation in rats.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations